Influences of the 2010 Eyjafjallajökull volcanic plume on air quality in the northern Alpine region - Schäfer, K.; Thomas, W.; Peters, A.; Ries, L.; Obleitner, F.; Schnelle-Kreis, J.; Birmili, W.; Diemer, J.; Fricke, W.; Junkermann, W.; Pitz, M.; Emeis, S.; et al. (München : European Geopyhsical Union, 2011)
A series of major eruptions of the Eyjafjallajökull volcano in Iceland started on 14 April 2010 and continued until the end of May 2010. The volcanic emissions moved over nearly the whole of Europe and were observed first on 16 April 2010 in Southern Germany with different remote sensing systems from the ground and space. Enhanced PM10 and SO2 concentrations were detected on 17 April at mountain stations (Zugspitze/Schneefernerhaus and Schauinsland) as well as in Innsbruck by in situ measurement devices. On 19 April intensive vertical mixing and advection along with clear-sky conditions facilitated the entrainment of volcanic material down to the ground. The subsequent formation of a stably stratified lower atmosphere with limited mixing near the ground during the evening of 19 April led to an additional enhancement of near-surface particle concentrations. Consequently, on 19 April and 20 April exceedances of the daily threshold value for particulate matter (PM10) were reported at nearly all monitoring stations of the North Alpine foothills as well as at mountain and valley stations in the northern Alps. The chemical analyses of ambient PM10 at monitoring stations of the North Alpine foothills yielded elevated Titanium concentrations on 19/20 April which prove the presence of volcanic plume material. Following this result the PM10 threshold exceedances are also associated with the volcanic plume. The entrainment of the volcanic plume material mainly affected the concentrations of coarse particles (>1 μm) – interpreted as volcanic ash – and ultrafine particles (<100 nm), while the concentrations of accumulation mode aerosol (0.1–1 μm) were not changed significantly. With regard to the occurrence of ultrafine particles, it is concluded that their formation was triggered by high sulphuric acid concentrations which are necessarily generated by the photochemical processes in a plume rich in sulphur dioxide under high solar irradiance. It became evident that during the course of several days, the ...